Organizational effectiveness revisited: Integrating equity, access, and inclusion in higher education frameworks — an integrative review - Alam, Muhammad Masroor; Dubey, Suchi (Edelweiss Applied Science and Technology, 2025)
The objective of this study was to examine how organizational effectiveness (OE) frameworks in higher education institutions (HEIs) integrate diversity, equity, and inclusiveness (DEI) in relation to student access, participation, and completion. To achieve this goal, an integrative review of 23 peer-reviewed studies published between 1978 and 2024 was conducted, applying a theory-informed thematic analysis to synthesize evidence across multiple contexts. The review identified five key dimensions through which inclusiveness is explicitly or implicitly embedded within OE frameworks: institutional performance, access and retention, cultural and social inclusion, policies for sustainability and structural inclusiveness, and faculty and leadership development. Although traditional OE models emphasize efficiency and strategic alignment, the analysis reveals a gradual shift toward equity-oriented indicators that remain inconsistently implemented and weakly institutionalized. Rather than proposing a definitive model, this review establishes a conceptual foundation for rethinking institutional effectiveness through an inclusive perspective. The findings highlight the potential of technology-enabled systems such as institutional dashboards, analytics-based quality assurance tools, and student-tracking mechanisms—to translate inclusiveness into measurable institutional outcomes, thereby strengthening the applied and policy relevance of organizational effectiveness research in higher education.